A Dermatoglyphic Study of Primary Fingerprints Pattern in Relation to Gender and Blood Group Among Residents of Kathmandu Valley, Nepal - Sushma Paudel; Sushmita Paudel; Samikshya Kafle (IET Biometrics)
Fingerprints are unique biometric identifiers that reflect intricate genetic and environmental/physiological influences. Beyond their forensic significance, they can offer insights into physiological traits like blood groups and gender, which can help in forensic analysis to narrow down the search. This exploratory study aims to identify potential associations between fingerprint patterns, gender, and blood groups within a defined regional cohort in Kathmandu, Nepal. This preliminary study included 290 students (144 males and 146 females) from Himalayan Whitehouse International College (HWIC). Fingerprint patterns (loops, whorls, and arches) were analyzed and compared with participants’ ABO-Rh blood groups. Statistical analyses, including chi-square tests, were used to determine associations and trends. Loops emerged as the most common fingerprint pattern (57.14%), followed by whorls (35%), and arches (7.86%). Blood group B+ve was the most prevalent (33.1%) among the study population in Kathmandu. The significant association between gender and fingerprint pattern was observed. The gender analysis revealed that loops were predominant in females, while males showed a higher frequency of whorls. While no significant relationship was observed between ABO blood groups and fingerprint patterns, a strong association was found between fingerprint patterns and Rh factor (p=0.0496). Loops were more prevalent among Rh-positive (Rh+ve) individuals, while whorls were more common among Rh-negative (Rh−ve) individuals. Additionally, specific fingers were observed to have distinct fingerprint patterns more frequently. Arches were most prevalent in the index finger of both hands, loops were most abundant in both pinky finger, and left middle finger. Whorls were most frequently observed in ring finger of both hands and right thumb. The findings reinforce global patterns of blood group and fingerprint distribution, where Rh+ve individuals represent the majority and loops are most dominant fingerprint pattern. The gender-specific trends suggest the nuanced interplay of genetics, with females displaying a higher frequency of loops and males showing more whorls. Similarly, some blood group are more likely to exhibit a specific set of fingerprint patterns. This research clearly shows the gender-based differences and influence of genetic factors on fingerprint patterns, particularly the Rh factor. These findings contribute to the growing field of dermatoglyphics, with implications for forensic science, and population genetics.